2005
DOI: 10.1136/sti.2004.012328
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of HIV among black and minority ethnic men who have sex with men in England and Wales

Abstract: Objectives: To examine the epidemiology of HIV among black and minority ethnic (BME) men who have sex with men (MSM) in England and Wales (E&W). Methods: Ethnicity data from two national HIV/AIDS surveillance systems were reviewed (1997-2002 inclusive), providing information on new HIV diagnoses and those accessing NHS HIV treatment and care services. In addition, undiagnosed HIV prevalence among MSM attending 14 genitourinary medicine (GUM) clinics participating in the Unlinked Anonymous Prevalence Monitorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 13 publications
1
38
0
1
Order By: Relevance
“…The number of MSM with diagnosed HIV currently stands at more than 33,600 (Aghaizu et al, 2013) with a disproportionately high burden of infection among black and minority ethnic MSM (Dougan et al, 2005). The desire to have sex does not, of course, cease at diagnosis and many MSM with diagnosed HIV continue to have active sexual lives, although these are often compromised by the effects of HIV stigma and rejection by sexual partners (Bourne, Hickson, Keogh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The number of MSM with diagnosed HIV currently stands at more than 33,600 (Aghaizu et al, 2013) with a disproportionately high burden of infection among black and minority ethnic MSM (Dougan et al, 2005). The desire to have sex does not, of course, cease at diagnosis and many MSM with diagnosed HIV continue to have active sexual lives, although these are often compromised by the effects of HIV stigma and rejection by sexual partners (Bourne, Hickson, Keogh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The general consensus among the major sexual health reports and articles is that MSM stands for "Men who have Sex with Men" (e.g., Dougan 2005;Elford 2010;Hickson 2004;Prost et al 2008). However in terms of operationalisation, there are three variables we have identified that are not accounted for in this classification, and also are not often addressed in reports and articles about MSM: type of sex, gender, and habitualness.…”
Section: Defining "Msm"mentioning
confidence: 91%
“…Using the ONS census categorisations to describe the ethnic populations in the UK, generally speaking, a large majority of the organisations agree that the term BME includes the aggregated Black, Mixed, Asian, Chinese, and Other ethnic groups (e.g., Dougan et al 2005;Hickson et al 2004;POST 2007;Raleigh et al 2010). It is also generally accepted that the "White British" category (comprising of English, Welsh, and Scottish) describes the ethnic majority and therefore is not included in the BME designation in each case reviewed.…”
Section: Bme and Msmmentioning
confidence: 99%
“…BME MSM face a double jeopardy in relation to sexual health. Black MSM are more likely to be diagnosed with a bacterial sexually transmitted infection (STI) compared to other ethnic groups (Dougan et al, 2005), and this group is 15 times more likely to be HIV-positive compared with the general population (Millet et al, 2012). According to recent Public Health England HIV surveillance data (Public Health England, 2015), there has been a more than 82% increase in new HIV diagnoses among MSM of "other" and mixed heritage.…”
Section: Introductionmentioning
confidence: 99%